2015
DOI: 10.1590/1516-1439.000515
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Behavior of Carbon Fiber/Phenolic Composite during Pyrolysis

Abstract: Carbon fiber reinforced carbon (CFRC) composites, also called carbon/carbon (C/C) composites are materials with superior characteristics such as low density, good thermal shock resistance, high strength and low ablation under severe environments. Due to their properties, CFRC composites are ideal candidate in the high temperature fields. By pyrolysis process, carbon fiber phenolic resin composites are converted in C/C composites. The phenolic resin is a non-conductor (electrical resistivity of 1012 Ω.m) and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The condensation of molecules from aromatic rings and the volatilization of these compounds lead to the weight loss and shrinkage of the phenolic resin. 36,37,39 At about 700 C, the phenolic resin is then converted slowly to amorphous carbon.…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The condensation of molecules from aromatic rings and the volatilization of these compounds lead to the weight loss and shrinkage of the phenolic resin. 36,37,39 At about 700 C, the phenolic resin is then converted slowly to amorphous carbon.…”
Section: Thermal Analysismentioning
confidence: 99%
“…From the DTG plots, there are two prominent peaks for both resins; the first peak lies in the temperature range of 100-130 C while the second lies in the range 460-550 C. The first peak is due to the curing reaction, while the second peak is due to the decomposition of the phenolic resin leaving behind a carbonaceous residue. [36][37][38] According to De Souza et al, 37 there are no significant molecular size changes up to 350 C; only small molecular bridge transformations occur because of the release of volatile free molecules, notably water and phenol. As the curing reaction started, the increase in these activated volatile free molecules gave rise to the monotonic increase in the DTG curve until it got to the maximum temperature of 100-130 C for both phenolic resoles.…”
Section: Thermal Analysismentioning
confidence: 99%
“…The model assumed an initial electric conductivity until the onset of material decomposition, during decomposition the electrical conductivity was assumed to increase linearly, at 800 o C the epoxy was assumed to ablate and above this temperature a fully conductive value of electric conductivity was modelled (1x10 6 1/ Ω.mm). This relationship was based on TGA experiments within literature for epoxy [32]- [34]. In this case the energy released during resin decomposition was the same as that used for the unprotected laminate.…”
Section: Thermal-electric Damage Modellingmentioning
confidence: 99%
“…Because of the presence of phenolic compounds such as phenol, 4-(1-methylethyl)-, phenol, p-tert-butyl-, p-isopropenylphenol, phenol, 4,4′-(1-methylethylidene)bis in the sC2 sample, the weight loss was estimated to be less in the TG–DTG curve measured from room temperature to 600 °C. Zhou et al and Souza et al reported the thermal decomposition of a phenolic resin converted to an amorphous carbon at 700 °C, and showed that the thermogravimetric loss rate of pure phenolic resin reached a maximum at 550 °C 27 , 28 .
Figure 8 TG–DTG curves of Case III evidence.
…”
Section: Resultsmentioning
confidence: 99%